Analisis Kinerja Reksadana Saham Syariah Di Pasar Modal Indonesia Menggunakan Metode Sharpe, Treynor, Dan Jensen Periode 2017-2018 - Abdul Hamid, Ahmad Karim; Cahyadi, Iwan Fahri (IAIN Kudus, 2019)
This research aims to find out the performance of sharia stock mutual funds in the Indonesian Capital Market based on sharpe, treynor and jensen methods and to find out the comparison of the performance of sharia stock mutual funds with benchmark performance in the research period of 2017-2018. This type of research is evaluative research with a quantitative approach. The population in this study includes all sharia mutual funds registered and still active in the Financial Services Authority (OJK) until December 2018. Sampling techniques used purposive sampling techniques and obtained 23 sharia stock mutual funds as a research sample. Data analysis techniques are descriptively analyzed, the data obtained is collected and then processed with the appropriate formulas on the operational definition of measurement and research variables. Data analysis techniques are descriptively analyzed, the data obtained is collected and then processed with the appropriate formulas on the operational definition of measurement and research variables. To make data processing easier using microsoft excel programs. Based on the analysis of islamic stock fund performance data according to sharpe method in 2017 there are 7 sharia stock mutual funds that show positive performance, and in 2018 there were 3 sharia stock mutual funds showing positive performance. Meanwhile, according to treynor method in 2017 there were 7 sharia stock mutual funds that showed positive performance, and in 2018 there were 3 sharia stock mutual funds that showed positive performance. Meanwhile, according to jensen method in 2017 there are 6 sharia stock mutual funds that showed positive performance, and in 2018 there were 5 sharia stock mutual funds that showed positive performance. Based on the results of the comparison of the performance of sharia stock mutual funds with benchmarks in the period 2017 according to sharpe method there are 5 sharia stock mutual funds that have outperform performance, and in the period 2018 there are 3 sharia stock mutual funds that have outperform performance. Meanwhile, according to treynor method in 2017 there are 1 sharia stock mutual fund that has outperform performance, and in 2018 there are 20 sharia stock mutual funds that have outperform performance. While according to jensen method in 2017 there are no sharia stock mutual funds that have outperform performance, and in the period 2018 there are 23 sharia stock mutual funds that have outperform performance. And there are 2 sharia stock mutual funds that consistently perform best against market performance during the research period, namely Sucorinvest Sharia Equity Fund sharia stock mutual fund and Sharia Pacific Saham Syariah stock fund.